Isolation of Fibrillar Elastin Gel (FEG) and its application in heart valve tissue engineering - Iftekhar, S (2020)
Elastin, although a small constituent of heart valves, plays a significant role in its functionality and the maintenance of tissue homeostasis. It is due to its low abundance that its significance has been overlooked in favour of collagen and glycosaminoglycans. However, repeatedly, the failure of biological prostheses has been associated with the disruption of elastic fibres. The incorporation of exogenous forms of elastin has been challenging due to the intrinsic insolubility and poor processability of polymeric forms. This has led to the precedence of applications of soluble forms of elastin, which, although are tailorable, do not offer sufficient structural integrity or bioactivity (once cross-linked).